FAKTOR KETERLAMBATAN BERBICARA PADA ANAK; KAJIAN PSIKOLINGUISTIK DALAM PEMBELAJARAN BAHASA - Alwandi Yanta Krisna (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This research have a purpause to describe the factors that cause children's delay in speaking. The approach used in this research is a qualitative approach. While the type of research is literature study. The data source for this research is relevant research articles. The data of this research is the result of relevant research. To validate, researchers use data triangulation. The data analysis technique used is an interactive analysis technique. The results showed that the factors that cause speech delays in children are internal factors consisting of genetics and also the hormone testosterone. While the external factors that cause delays in speaking are family, school and society. Therefore, cooperation in child supervision is needed starting from the family, school and community environment through medical and social supervision. It is hoped that this research will become an evaluation in monitoring the growth and development of children with speech delays.